(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The purpose of studying the history of the language is to study the development of the language from the very earliest time up to days. At the same time studying the history of the language we shall have some knowledge about the history of England and English people and its literature. Naturally, the history of the language specially the phonetics is studied diachronically.